MAINTENANCE STRATEGY REVIEW (MSR) BASED ON ISO 14224:2016 IN INDONESIA OIL AND NATURAL GAS COMPANIES - Setyoko, Ajun Tri; Nurcahyo, Rahmat; Adipraja, Aulia Sena; Budiono, Hendri Dwi Saptrioratri (JURNAL STANDARDISASI, 2024)
The oil and gas industry is vital for Indonesia, and the safety and effectiveness of work in processing and exploring the oil and gas that operate in Indonesia must comply with existing regulations. This safety and effectiveness are inseparable from how the company maintains the assets and instruments used at the oil and gas production and exploration site. Maintenance of pipes and instruments for production is one of the company's most vital assets. In addition to having appropriate productivity, pipes and instruments must be maintained optimally so that maintenance costs do not exceed the value of the oil and gas production. This study's research subject is a natural gas refinery from an oil and gas company operating in the Madura Strait, East Java, Indonesia. The object of research limited to the company's piping system (pipeline system). This study uses a quantitative assessment using the calculated Mean Time Before Failure (MTBF) method and a qualitative assessment using the asset maintenance standard to  reveals how the maintenance cycle that has been implemented can be optimized. The author carried out a criticality assessment using Maintenance Strategy Review (MSR) to calculate the risk level of asset. This study found that 78 assets must be maintained in their maintenance cycle, two cash assets must be reduced in their maintenance cycle, and seven assets can be extended for their maintenance cycle. The two assets that need to be reduced in maintenance cycles are the shutdown valve asset that goes to the temporary pig receiver and the shutdown valve that goes to the HP flare header. An asset that can be extended its maintenance cycle is a transmitter for flow indicators.